Age-dependent elevations of oligomeric and phosphorylated alpha-synuclein synchronously occurs in the brain and gastrointestinal tract of cynomolgus monkeys. (1st January 2018) - Li, Xin; Yang, Weiwei; Li, Xuran; Chen, Min; Liu, Chengwei; Yu, Shun
Highlights: Oligomeric and phosphorylated α-synucleins increase with age in the gut and brain. Age-dependent α-synuclein oligomerization correlates between the colon and brain. Age-dependent α-synuclein phosphorylation correlates between the colon and brain. Abstract: Fibrillary α-synuclein (α-syn), which constitutes the major component of Lewy pathology characterized for Parkinson's disease (PD), is found also in the aged enteric nervous system (ENS) and central nervous system (CNS). However, what happens to oligomeric α-syn (o-α-syn) in the aged ENS and CNS remains poorly understood. Here, by using ELISA methods specific for o-α-syn and phosphorylated α-syn (p-α-syn), we measured the levels of o-α-syn and p-α-syn in the gastrointestinal (GI) tract and brain of aging cynomolgus monkeys. We detected a synchronously occurred age-dependent elevation of o-α-syn in the GI tract and brain, which was accompanied by an age-dependent increase of α-syn phosphorylated at serine 129, a modification that promotes α-syn aggregation. Correlation analysis revealed that alterations in p-α-syn and o-α-syn in the colon were positively correlated to those in some brain regions such as the striatum, hippocampus, thalamus and temporal lobe. The results obtained suggest that age-dependent elevations of p-α-syn and o-α-syn occur synchronously in various regions of the ENS and CNS.